Γ-Rays Irradiation Induced Structural and Morphological Changes in Copper Nanowires. (20th September 2016) - Shehla, H.; Thema, F. T.; Ishaq, A.; Ali, Naveed Zafar; Javed, I.; Wan, D.; Maaza, M.
Abstract : This contribution reports on the effect of γ -irradiations on the structural and morphological properties of copper nanowires (Cu-NWs) within the γ doses varying from 6 to 25 kGy. At 9 kGy, the Cu-NWs started welding, forming perfect X-, V-, II-, and Y-shaped molecular junctions. Further increasing the γ dose up to 15 kGy caused the Cu-NWs to fuse and form larger diameter NWs. At the highest dose of 25 kGy, the nanowires converted into a continuous Cu thin film. However, X-ray diffraction (XRD) results showed that the structure of the Cu-NWs remained stable even after converting into a thin film. The formation of the Cuprite (Cu2 O) phases was observed at higher γ dose. The mechanism of forming welded networks of Cu-NWs and Cu thin films is explained via the short and high energy γ -ray wavelengths which act on Cu-Cu molecular covalent bonds isotropically.